Oral changes in individuals undergoing hematopoietic stem cell transplantation - Barrach,Regina Haddad (2015)
INTRODUCTION: Patients undergoing hematopoietic stem cell transplantation receive high doses of chemotherapy and radiotherapy, which cause severe immunosuppression.OBJECTIVE: To report an oral disease management protocol before and after hematopoietic stem cell transplantation.METHODS: A prospective study was carried out with 65 patients aged > 18 years, with hematological diseases, who were allocated into two groups: A (allogeneic transplant, 34 patients); B (autologous transplant, 31 patients). A total of three dental status assessments were performed: in the pre-transplantation period (moment 1), one week after stem cell infusion (moment 2), and 100 days after transplantation (moment 3). In each moment, oral changes were assigned scores and classified as mild, moderate, and severe risks.RESULTS: The most frequent pathological conditions were gingivitis, pericoronitis in the third molar region, and ulcers at the third moment assessments. However, at moments 2 and 3, the most common disease was mucositis associated with toxicity from the drugs used in the immunosuppression.CONCLUSION: Mucositis accounted for the increased score and potential risk of clinical complications. Gingivitis, ulcers, and pericoronitis were other changes identified as potential risk factors for clinical complications.